Sistem Informasi Rekapitulasi Pemilukada Kota Pekanbaru menggunakan Input dari Telegram API - Brima Zidane Ferdiyan; Erwin Setyo Nugroho (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
In the process of the regional head election, there is a recapitulation process for the vote acquisition conducted by the KPPS (Voting Organizers Group) at each TPS (polling station). Where this process usually takes a very long time and also causes a lot of problems. In Pekanbaru City, the information on the recapitulation of the regional head election sent to the candidate pairs or the supporting party was still based on the SMS (Short Message Service) gateway which made the candidate pairs/supporting parties have to do the recapitulation manually again. From these problems, the Pekanbaru City Regional Head Election Recapitulation Information System was built using Inputs from the Telegram API that can solve these problems. From the results of testing the black box on the system by following the ISO 9126-2 standard, the results on each metric have a number of 1 and an average of 1 which means that the system's functions are in accordance with needs and expectations. In performance testing the average delay time when the bot is sent data in the form of images (command /c1) is 4.447 seconds, while when the bot is sent data in the form of text/numbers (commands other than /c1) the average delay time is less than 1.5 seconds. In the user acceptance testing, this information system is very helpful for the candidate pair and the bearer party in conducting vote recapitulation during the regional head election process and also get the results of the recapitulation of votes with detail and realtime.